MANAJEMEN PROGRAM LINK AND MATCH PADA PROGRAM KEAHLIAN TATA BUSANA DI SMK SYAFI’I AKRAM PEKALONGAN - Tri Sari Wulansih; Ngurah Ayu Nyoman M; Soedjono (STKIP Subang, 2023)
The Link and Match Program is implemented to enhance the absorption of SMK graduates into the industry and the workforce. The focus of this research is the management of the Link and Match program in the Fashion Design Vocational Program at SMK Syafi'i Akram Pekalongan. The aim of this research is to obtain information about the planning, organization, implementation, and monitoring processes of the Link and Match program in the fashion design vocational program at SMK Syafi'i Akram Pekalongan, located at Jl. Pelita 1 No. 322, Pekalongan City, from March to September 2023. The research employs a qualitative approach, and data is collected through observation, documentation, and in-depth interviews. Information sources for this research include the School Principal, Vice Principal, BKK (Employment Office) representatives, Head of the Fashion Design Vocational Program, Fashion Design Vocational Program teachers, representatives of 12th-grade students, and industry representatives. Data validity is ensured through source and technique triangulation. Data analysis techniques involve data collection, presentation, data condensation, and drawing conclusions. Research findings: a) Planning includes coordination activities, determining the integration of the 8+i link and match concept into the curriculum, mapping and analyzing student and alumni data, mapping and selecting partner businesses and industries, and promoting the implementation of the link and match program. b) Organization involves mapping available school resources and assigning workgroups. c) Implementation encompasses curriculum alignment with partner businesses and industries, project-based real-life learning and teaching factory, guest teaching by industry professionals, internships or work placements for teachers and students, competency certification in line with industry standards and workforce needs for graduates and teachers, technology updates, and training from the industry for teachers and students, as well as graduate absorption commitment. d) Monitoring includes internal supervision by the School Principal and external supervision involving partner businesses and industries. The conclusion of this research is that management activities, particularly in the implementation phase, have effectively implemented the 8+i link and match concept for SMK Syafi'i Akram Pekalongan, following the directives of the Directorate General of Vocational Education, Ministry of Education, Culture, Research, and Technology. Recommendations include strengthening partnerships with a larger and more innovative number of businesses and industries to enhance the competencies of fashion design vocational program students, thus ensuring high absorption rates in terms of both quantity and quality.